INTERPRETATION AND INTERNALIZATION OF MODERATION VALUES IN PONDOK MODERN DARUSSALAM GONTOR - Anam, Khoirul; Kadir, Abdul; Rofiq, Aunur (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2023)
Abstract: This article presents research results on moderation (wasthiyyah) values at Pondok Modern Darussalam Gontor. This study uses a qualitative descriptive method to describe the interpretation and internalization of the values   of moderation in Pondok Modern Darussalam Gontor education. Data were collected by interview, observation, and documentation methods. The results of the study concluded that the values   of moderation in Pondok Modern Darussalam Gontor are interpreted as an integral part of the Five Souls of Pondok Modern Darussalam Gontor which include: a soul of sincerity, a spirit of simplicity, a spirit of independence, a spirit of Islamic brotherhood and a spirit of freedom. The values of moderation in the five souls are comprehensively internalized in every breath, movement and step in every educational activity and practice through a continuous educational process with an independent, structured and systematized curriculum through typical disciplined patterns and lifestyles.Keywords: Value, Moderation, Internalization, Gontor